Model Design For Change (DFC) Sebagai Upaya Penyelesaian Masalah Secara Mandiri Pada Santri Putra Kelas X MA Al-Falah Padang - Ahmad Putra (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2022)
This study aims to find out how the implementation of the design for change (DFC) model is one of the models/services that aims to build a person's ability to find solutions to a problem, but this service is estimated to be rarely introduced at the high school level, especially in tutoring subjects. school counselling. The counseling guidance teacher at Madrasah Aliyah Al-Falah Padang tries to practice this DFC model for the tenth grade students of Madrasah Aliyah with the aim of building the students' independence and ability to solve the problems they experience. This research is a field research using a qualitative approach. The subjects in this field research were 5 students of class X Madrasah Aliyah and 2 teachers of counseling guidance. Collecting data through observation, interviews (interviews) and documentation. The results obtained from the application and use of this DFC model are that students' independence is built to try to solve problems they encounter or are currently experiencing, and train students to be tough when facing a problem